Imports matter more than you think: a complexity-weighted reassessment of trade and GDP growth - Zhang, Yutai; Zhou, Yihua; Fan, Niuniu; Sun, Xinyue; Pang, Siqing; Yang, Liangli; Lei, Jieqi; Wu, Ruijie; Kong, Yixiu (Frontiers in Physics, 2025)
Gross Domestic Product (GDP), as a key indicator of a country’s economic performance, is often assumed to have a positive correlation with Net Exports based on the expenditure approach to GDP calculation. However, by introducing the product complexity that integrates a product’s technological content and scarcity of international trade, we investigate the impact of trade complexity on GDP growth across all countries within our data. Our findings reveal a significant negative correlation between net Complexity-Weighted Exports and GDP, contrasting with traditional belief. Further analysis discovers that Complexity-Weighted Imports (CWI) has a more pronounced effect on GDP than Complexity-Weighted Exports (CWE), underscoring the crucial role of imports in driving economic growth. To establish a universal model for analyzing the impact patterns of CWE and CWI on GDP, we employed a Long Short-Term Memory (LSTM) neural network to model and analyze relevant data from the majority of countries worldwide. Through this model, we explored the import and export adjustment strategies a country should adopt at different stages of economic development. Our study demonstrates a significant positive correlation between the importation of high-complexity products and a nation’s GDP, which also suggests that imported products may facilitate non-linear GDP growth within the domestic economy. These findings offer a reference for how countries can formulate macroeconomic strategies for imports and exports to stimulate economic growth.